Irrigation with primary wastewater alters wood anatomy and composition in willow Salix miyabeana SX67 - Jerbi, Ahmed; Laur, Joan; Lajoie, Kevin; Gallant, Pierre-Paul; Barnabé, Simon; Pitre, Frederic E.; Labrecque, Michel (Frontiers in Plant Science, 2023)
Traditional treatment of wastewaters is a burden for local governments. Using short rotation coppice willow (SRCW) as vegetal filter has several environmental and economic benefits. Here, we investigated the effect of primary wastewater irrigation on wood structure and composition of the willow cultivar Salix miyabeana ‘SX67’ following two years of growth. Compared to unirrigated plants (UI), stem sections of plants irrigated with primary wastewater (WWD) showed an unexpected decrease of hydraulic conductance (KS) associated with a decrease in vessel density but not vessel diameter. The majority (86 % ) of vessels had diameters range groups [20-30[, [30-40[ and [40-50[ µm and contributed to > 75 % of theoretical KS, while the group class [50-60[ µm (less than 10 % of vessels) still accounted for > 20 % of total KS regardless irrigation treatments. WWD significantly alters the chemical composition of wood with an increase of glucan content by 9 to 16.4 % and a decrease of extractives by 35.3 to 36.4 % when compared to UI or to plants irrigated with potable water (PW). The fertigation did also increase the proportion of the tension wood which highly correlated with glucan content. In the context of energetic transition and mitigation of climate change, such results are of high interest since WWD effectively permit the phytofiltration of large amounts of organic contaminated effluents without impairing SRCW physiology.